2010
DOI: 10.1080/13683500903576045
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate change on Caribbean tourism demand

Abstract: Climate change can either positively or negatively impact on the attractiveness of a destination. To evaluate the potential effects of these changes for Caribbean destinations, a cross-country tourism demand model is augmented with relative tourism climatic indices to examine the importance of an island's climatic features. The model is estimated using a dynamic panel approach and monthly observations over the period . Combining the scenarios for future climatic conditions as well as the coefficient estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 18 publications
2
74
0
Order By: Relevance
“…A direct impact of climate change on tourism will be the global redistribution of climatic resources, which will affect the temporal and spatial distribution of domestic and international tourism flows and economic spending [94]. An increasing number of publications have sought to analyze how travel flows could be altered by climate change [57,60,61,63,64,[95][96][97][98][99][100][101]. The results from these publications are meant to identify potentially vulnerable destinations and assist the tourism industry in planning future operations, including the development of adaptation strategies to minimize associated risks and capitalize on new opportunities posed by changes in the competitive relationships among destinations [98].…”
Section: Discussionmentioning
confidence: 99%
“…A direct impact of climate change on tourism will be the global redistribution of climatic resources, which will affect the temporal and spatial distribution of domestic and international tourism flows and economic spending [94]. An increasing number of publications have sought to analyze how travel flows could be altered by climate change [57,60,61,63,64,[95][96][97][98][99][100][101]. The results from these publications are meant to identify potentially vulnerable destinations and assist the tourism industry in planning future operations, including the development of adaptation strategies to minimize associated risks and capitalize on new opportunities posed by changes in the competitive relationships among destinations [98].…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the nutmeg and cocoa industries due to hurricane Ivan in 2004 resulted in loss equivalent to 10% of Grenada's GDP (Mimura et al, 2007). Under future climate change, 46% of Caricom tourist resorts could be lost under a 1 m rise in sea-level (Moore, 2010;Simpson et al, 2010), while projected changes in temperature and rainfall will likely increase crop pests and diseases and the occurrence of extreme water stress (Nelson et al, 2009;Pulwarty et al, 2010;Simpson et al, 2010;Cashman et al, 2010). Past and future climate impacts on other key areas of Caribbean existence, for example, biodiversity and marine and coastal ecosystems (e.g., Fish et al, 2005;Donner et al, 2007;Hoegh-Guldberg et al, 2007;Chen et al, 2008) and on health and well being (e.g., Amarakoon et al, 2006;Chen et al, 2006;Ebi et al, 2006;Taylor et al, 2009) have also been studied and shown to be significant.…”
Section: Introductionmentioning
confidence: 99%
“…the tourism sector in many tropical nations is based heavily on the sun, sea, and sand attractions (briguglio, Archer, Jafari, & wall, 1996, p. 206), making climate a key determining factor in the decisionmaking process for tourists (Uyarra et al, 2005). therefore, tourism is highly sensitive to changes to the climate and natural resources (Moore, 2010;Payet, 2008;. Sea level rise and resultant inundation from storm surges threaten coastal tourism infrastructure (belle & bramwell, 2005; Commonwealth of Australia, 2011;richardson & witkowsky, 2010) and communities (buultjens, white, & willacy, 2007).…”
mentioning
confidence: 99%